Doppler study (cerebroplacental ratio) as a predictor of adverse perinatal outcome - Sengodan, Subha S.; Mathiyalagan, Sankari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Objective of the current study was to determine the importance of Doppler screening (cerebroplacental ratio i.e. CPR) in antenatal mothers and its effect on perinatal outcome of the baby so that appropriate management can be planned effectively for a better reduction in perinatal mortality and morbidity. Methods: A prospective study conducted on hundred antenatal women in GMKMCH, Salem with gestational age >32 weeks, with singleton pregnancies. Doppler ultrasonogram of fetal middle cerebral artery and umbilical artery and thus CPR obtained. Results: 25 out of the 100 patients in the study had CPR<1. CPR was compared against factors such as maternal age, parity, associated risk factors, gestational age (GA) at diagnosis (LMP GA and scan GA), time duration to delivery from diagnosis, requiring neonatal intensive care unit (NICU) admission, duration of stay in NICU and perinatal mortality. The CPR≤1 has a good sensitivity of 68% but a very high specificity of around 98% in predicting neonatal complications which was found to be statistically significant with a p value <0.0001. Conclusions: Since CPR has a high negative predictive value, CPR>1 helps to rule out adverse perinatal outcomes. When CPR<1, it acts as an effective tool in helping the obstetrician to decide on the mode of delivery to ensure that the baby is delivered within 12 hours of diagnosis, to improve the perinatal outcome of the baby.